Doing justice-reporting court-reporting : problems and recommendations - Siason, Deserie A. 1990- (2012)
"This thesis describes the court-reporting practices of the journalists assigned in the Supreme Court. It also examines the reasons why court-reporting has become problematic for journalists, the public and the news subjects: the courts, the justices and the litigants. "Legal Journalism", more commonly known as court-reporting, is the practice of promoting knowledge of the judiciary and understanding of the country's civil and criminal justice system to the public which is essential to democracy. This study uses Framing theory of communication which presumes that people use frames as cognitive shortcuts to help make sense of complex information. The researcher was able to look at the current state of "legal journalism" in the print and broadcast media using a combination of quantitative and qualitative approach. The discussion is drawn from the data gathered from books and journals on court coverage, from interviews with key informants; selected for their valuable insights into the practical applications of "legal journalism" in the Philippine Supreme Court, and from the survey of 100 respondents on their reception of the ongoing impeachment trial coverage of Chief Justice Renato Corona. This study aims to serve as a tool in further developing "legal journalism" in the Philippines."